Pragmatism, ideology or politics? Trade unions and workers : responses to the imposition of neo-liberalism in Argentina (1976-2010) - Atzeni, Maurizio (2011)
Fil: Ghigliani, Pablo. Universidad Nacional de La Plata. Facultad de Humanidades y Ciencias de la Educación. Instituto de Investigaciones en Humanidades y Ciencias Sociales (UNLP-CONICET); Argentina.